Legal Analysis of Lease Agreements Without Written Deeds - Amalia Tasya (PT. Anagata Sembagi Education, 2024)
Lease agreements are one form of contract that is common in society, both in the fields of property, vehicles, and other movable goods. In practice, many of these agreements are made verbally or without a written deed. This article aims to analyze the legal validity of lease agreements without a written deed based on the Civil Code (KUH Perdata) and examine its legal implications in social practice. Using normative legal methods and sociological approaches, it was found that oral lease agreements remain valid as long as they meet the requirements for a valid agreement as regulated in Article 1320 of the Civil Code. However, the absence of written documents has the potential to cause disputes, especially in proof before the law. Legal awareness and contractual education are needed so that the public better understands the importance of written agreements as legal evidence.